2022
DOI: 10.1149/1945-7111/acadb1
|View full text |Cite
|
Sign up to set email alerts
|

S, N and Cl Separately Doped Graphene Oxide/Polyaniline Composites for Hybrid Supercapacitor Electrode

Abstract: Conducting polymer and carbon-based materials are important in supercapacitor applications as capacitive materials. However, the use of these materials alone limits their application due to poor rate capability and short lifetime or low capacitance. Herein, the supercapacitor electrodes were successfully synthesized by two step process on the carbon-felt. Firstly, S-GO, N-GO and Cl-GO was obtained by chronoamperometry method at room temperature. After, PANI composites were synthesized through a hydrothermal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…The resulting layered and fiber-containing structures were compatible with the classical PANI structure. 37,61,62 It was seen that the material structure produced layered (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting layered and fiber-containing structures were compatible with the classical PANI structure. 37,61,62 It was seen that the material structure produced layered (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…7,35,36 Especially, doping of graphene by sulfur and nitrogen radically increased specific capacitance of the supercapacitor. 37 Yazar et al (2023) showed the effects of heteroatom doping on the electrochemical behaviors of the graphene based materials. 37 In each doping process, graphene-based materials are doped with different functional groups of these atoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the determination of the capacitance of each sample, eqn (2) and (3) derived from cyclic voltammetry and galvanostatic charge/discharge testing, respectively, were applied:where C is the specific capacitance (F g −1 ), is the integrated area under the C – V curve, Δ V (V) is the operating potential window, m (g) is the weight of the active electrode material, v (V s −1 ) is the applied scan rate, I (A) is the discharge current and Δ t is the discharge time (s). 28…”
Section: Methodsmentioning
confidence: 99%
“…where C is the specific capacitance (F g À1 ), H IdV is the integrated area under the C-V curve, DV (V) is the operating potential window, m (g) is the weight of the active electrode material, v (V s À1 ) is the applied scan rate, I (A) is the discharge current and Dt is the discharge time (s). 28…”
Section: Electrochemical Measurementsmentioning
confidence: 99%